2012
DOI: 10.1037/a0029043
|View full text |Cite
|
Sign up to set email alerts
|

Leader identity as an antecedent of the frequency and consistency of transformational, consideration, and abusive leadership behaviors.

Abstract: Drawing from identity-based theories of leadership, we examined relations of leader identity with leader behavior and perceived effectiveness. To do so, we employed multiwave methodology to examine the differential impact of leaders' chronic collective, relational, and individual identities on the frequency and consistency of their subsequent transformational, consideration, and abusive behaviors over a 3-week period. We also examined the relative importance of these leadership behaviors for predicting perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
244
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(257 citation statements)
references
References 72 publications
(137 reference statements)
13
244
0
Order By: Relevance
“…In contrast, this study has identified consideration leadership, which explains proportions of the variance 10.5 percent, as being a complement to transformational leadership in supporting employee creativity and innovation. This finding is consistent with other studies which emphasise that these two leadership behaviours increase leader effectiveness ratings, as they establish the leader as being stable and genuine in the view of the followers (Johnson et al, 2012). It is recommended that both leadership styles be incorporated into management training and development programmes.…”
Section: Discussionsupporting
confidence: 81%
“…In contrast, this study has identified consideration leadership, which explains proportions of the variance 10.5 percent, as being a complement to transformational leadership in supporting employee creativity and innovation. This finding is consistent with other studies which emphasise that these two leadership behaviours increase leader effectiveness ratings, as they establish the leader as being stable and genuine in the view of the followers (Johnson et al, 2012). It is recommended that both leadership styles be incorporated into management training and development programmes.…”
Section: Discussionsupporting
confidence: 81%
“…[33] Nurse leaders are likely to develop these positive work relationships when they identify with their healthcare organizations or unit as a collective, making a sense of group membership critical to leader relations. This collective identity is also perceived as more transformational in style by followers, [51] reinforcing the importance of positive social relationships within the workplace in promoting TL.…”
Section: Leader Relationsmentioning
confidence: 99%
“…Previous research has focused largely on one side of this interaction, namely, on follower identity, rather than attending to leader identity (Johnson et al, 2012;Kark & Van Dijk, 2007). Most research emphasises the identification of factors that have significant positive impacts on performance, such as the study conducted by , which aimed to examine the relationships between employee voice behaviour, employee identification, and transformational leadership, and the study conducted by Walumbwa and Hartnell (2011), concerning relational identification, self-efficacy, and transformational leadership.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is little wonder that current discussions of leadership tend to focus on interpersonal dynamics within the leadership process, particularly on how leaders engage followers and create positive effects that extend beyond task compliance Van Knippenberg et al, 2004). Among several key factors that influence the interaction between leaders and followers, current theory focuses on identity (Johnson et al, 2012;Van Knippenberg, 2011), which refers to the knowledge that individuals have about themselves (Johnson et al, 2012) that impacts the way they feel, think, and behave in relation to the things they seek to achieve (DeRue & Ashford, 2010;Van Knippenberg et al, 2004).…”
Section: Introductionmentioning
confidence: 99%